Basic properties of epigenetic systems: lessons from the centromere - Gómez-Rodríguez, Mariluz (2016)
Chromatin-based epigenetic inheritance cooperates with cis-acting DNA sequence information to propagate gene expression states and chromosome architecture across cell division cycles. Histone proteins and their modifications are central components of epigenetic systems but how, and to what extent, they are propagated is a matter of continued debate. Centromeric nucleosomes, marked by the histone H3 variant CENP-A, are stable across mitotic divisions and are assembled in a locus specific and cell cycle controlled manner. The mechanism of inheritance of this unique chromatin domain has important implications for how general nucleosome transmission is controlled in space and time.